Successful Anti-CLL1 CAR T-Cell Therapy in Secondary Acute Myeloid Leukemia - Zhang, Hui; Gan, Wen-Ting; Hao, Wen-Ge; Wang, Peng-Fei; Li, Zhuo-Yan; Chang, Lung-Ji (Frontiers in Oncology, 2020)
Secondary acute myeloid leukemia (sAML) is a high-risk AML evolving from heterogenous prior hematological disorders. Compared to de novo AML, sAML has even worse responses to current therapy and thus is associated with lower remission rates, inferior overall survival (OS) and higher relapse rates. Many efforts have been devoted to improving the overall but with limited success, and novel strategy is thus highly needed. Recent research has identified that CLL1 is highly expressed on AML leukemia stem cells and blasts cells but not on normal hematopoietic stem cells. In this case report, we treated a secondary AML patient with anti -CLL1 CAR-T therapy and achieved morphological, immunophenotypic and molecular complete remission for over 10 months. Although only one successful case is presented here, the anti-CLL1 CAR T-cells should be considered as another treatment option for secondary AML in the future.